The Approach of Sheikh Ahmed Mustafa Al-Maraghi in His Interpretation of The Noble Quran: A Critical Analysis Study - Gouda Gad, Mahmoud Mohamed Fathy; Abu-alhaj, Thabet Ahmad Abdallah; Ariffin, Sedek (Al-Basirah Journal, 2021)
The research deals with the approach of Sheikh Ahmed Mustafa Al-Maraghi in his interpretation of the Noble Quran, as a critical analysis study, and the research aims to know the approach of Sheikh Al-Maraghi in his interpretation for the Noble Quran, with an explanation of the advantages and disadvantages that were taken on the interpretation of Al-Maraghi, may Allah have mercy on him. On fundamental results, the most important of which are: that the interpretation of al-Maraghi is one of the interpretations of the modern mental school, and it combined the ease of presenting the interpretation with the clarity of the method, and the drawbacks that were taken on the interpretation of al-Maraghi resulted from the imitation of al-Maraghi of Imam Muhammad Abdo and Sheikh Rashid Rida, and I recommended the scientific and academic researchers to devote more studies on the approaches of Nobel Quran’s interpreters in the twentieth century, and to serve and investigate the interpretation of Sheikh Al-Maraghi in order to avoid the drawbacks that was taken about his interpretation , and to present it to the reader in an appropriate way. Keywords: